Parasitic infections status of the urban poor communities in Peninsular Malaysia - Mohd Zain, S.N. (2018)
Urban poor can be defined as a population in cities with household less than RM940 permonth (Economical Planning Unit, Department of Statistics Malaysia, 2018), measured quantitatively by Poverty Line Index (PLI). More accurately, it is the inability of the individuals in the urban areas to fulfill the requirement on achieving the minimum basic necessities of life including non-monetary indicators such as food, education, health, housing condition, household appliances and amenities (World Bank, 1990; Siwaretal. 1997; Sen, 1999; Rashidahetal, 2012; Samadetal, 2012; Chamcuri, 2016).